High-sensitivity room temperature p-doped and undoped GaN thin film resistive gas sensor. (25th July 2022) - Hasnan, M.; Asri, R.I.M.; Hassan, Z.; Abdalmohammed, S.A.A.; Nuzaihan, M.; Inaba, M.; Falina, S.; Syamsul, M.
The behaviour and performance of p-doped GaN and undoped GaN thin film in the presence of methanol gas were studied. GaN thin films were grown using metal organic chemical vapour deposition (MOCVD), which were then fabricated into resistive sensors. Gas-sensing characterisation with the in-house gas chamber demonstrates that the resistive sensors based on undoped and p-doped GaN exhibit high sensitivity and fast response to methanol vapour in less than a minute, as well as excellent stability in room temperature operations. Without high temperature measurements, both undoped and p-doped GaN resistive sensors exhibit significant resistance variation and response over time when exposed to methanol, albeit with distinct properties. Here we demonstrate the comparison between the two and their sensing capabilities of both p-doped GaN and undoped GaN thin film resistive sensors.